Criminal Procedure. Special Part : manual - Аркуша, Лариса Ігорівна; Аркуша, Л. І.; Arkusha, Larysa I.; Степаненко, Андрій Сергійович; Stepanenko, Andrii S.; Степаненко, А. С.; Степаненко, Оксана Василівна; Stepanenko, Oksana V.; Степаненко, О. В. (Odessa : Feniks, 2022)
The manual is designed for students of Criminal Procedure course for preparation to lessons and selfstudy. The manual consists of synopsis of the lectures course, seminar programme with questions and reading sections, questions for exam preparation and learning resources. It would be helpful for legal scholars, students, legal practitioners and anyone interested in criminal process of Ukraine.

Посібник призначений для студентів курсу Кримінальний процес, для підготовки до уроків і самостійної роботи. Посібник складається з конспекту курсу лекцій, програми семінарського заняття з запитаннями та розділами для читання, запитання для підготовки до іспиту та навчальні ресурси. Буде корисно для науковців, студентів, юристів-практиків та всіх, хто цікавиться кримінальним процесом України.
Criminal Procedure. Special Part : manual / L. I. Arkusha, A. S. Stepanenko, O. V. Stepanenko. – Odessa : Feniks, 2022. – 138 p. – Режим доступу: https://doi.org/10.32837/11300.18761
Keywords: pre-trial proceedings; court’s jurisdiction; preliminary proceedings; trial; review of court decisions in the court of appellate instance; досудове провадження; юрисдикція суду; попереднє провадження; суд; перегляд судових рішень в суді апеляційної інстанції; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law